Artificial Intelligence and the Future of Work: Empirical Insights from Human Resource Management in Libya - Shouran, Zaied; Abbas Ali, Dhakir (Journal of International Conference Proceedings, 2024)
Human resources (HR) and artificial intelligence (AI) have been the subject of numerous studies. This study looks at how the development of artificial intelligence and improvements in the oil sector affect human resource management. AI may be used by human resources (HR) professionals in recruiting and employee evaluations. By polling 200 HR experts from various Libyan oil businesses, the study aims to ascertain if the inventiveness and usability of HR operations influence the interaction between artificial intelligence and human resource functions in the Libyan oil sector. The hypothesis that these two variables are positively correlated was tested using multiple regression analysis. The results showed a relationship between better HR functional performance and a rise in the use of AI in the workplace. There is evidence, meanwhile, that artificial intelligence (AI) affects human resources in innovation and convenience. AI's utility and innovativeness are closely tied.